Why We Eat the Way We Do: A Call to Consider Food Culture in Public Health Initiatives - Edwina Mingay (MDPI AG, 2021)
The way we eat has changed dramatically in only a few decades. While definitions of food culture have previously existed, a clear description of modern food culture that can be used for health promotion is lacking. In this paper, we propose a concept of food culture for application within public health, what a positive food culture looks like compared to negative elements that have dominated in developed countries and the consequences for physical and mental health and wellbeing. We support calls to action from the international community to reconsider the way we eat. All segments of society have a role to play in building a positive food culture, and it is critical that macro (policy and systems) and meso (community) level environmental factors align and provide supportive environments that promote health-enhancing behaviours. Defining food culture is a necessary step towards articulating the complexities that influence food behaviours and impact health. The ultimate goal is collective action to enable population-wide and sustained improvements to the way we eat, and how we think and feel about food.